Moving beyond pain: the relationship between physical activity and physical self-concept among young women with endometriosis - Coquinos, Samantha; Oboeuf, Alexandre; Vitiello, Damien (Frontiers in Sports and Active Living, 2025)
BackgroundEndometriosis is a painful non-curable disease that affects women's quality of life, reducing their self-esteem and consequently their mental well-being. However, enhancing the physical self-concept could induce the development of the self-esteem. A suitable method to increase the physical self-concept would be physical activity (PA). The aim of this study was to evaluate the relationship between PA and physical self-concept in women with endometriosis under 30 years old and to evaluate whether the type of PA was associated with different physical self-concept scores.Materials and methodsA total of 198 women under 30 diagnosed with endometriosis responded to a survey. Physical self-concept was assessed using the short version of the physical self-description questionnaire. Women were also asked to answer to questions about their PA habits. The type of PA practiced was then assigned to 1 of the 3 following groups: relaxing activities (n = 14), activities without necessary interactions with other participants (n = 58), and activities including necessary interactions with other participants (n = 46).ResultsWomen under 30 years old participating in a regular PA (more than once a week) (n = 137) had a significantly higher physical self-concept than women not participating in a regular PA (n = 61) (p < 0.05). Results differed in physical self-concept sub-scales. The type of PA did not seem to make a difference in physical self-concept scores (p > 0.05).ConclusionYoung women with endometriosis should be advised to participate to a regular PA to increase their physical self-concept and therefore cope better with their anxiety and stress. All types of activities appear to be just as relevant for developing physical self-concept in young women with endometriosis.